Serum lactate levels in cirrhosis and non-cirrhosis patients with septic shock - Surat Tongyoo (2022)
Background: In septic shock patients with cirrhosis, impaired liver function might decrease lactate elimination and produce a higher lactate level. This study investigated differences in initial lactate, lactate clearance, and lactate utility between cirrhotic and non-cirrhotic septic shock patients. Methods: This is a retrospective cohort study conducted at a referral, university-affiliated medical center. We enrolled adults admitted during 2012-2018 who satisfied the septic shock diagnostic criteria of the Surviving Sepsis Campaign: 2012. Patients previously diagnosed with cirrhosis by an imaging modality were classified into the cirrhosis group. The initial lactate levels and levels 6 hours after resuscitation were measured and used to calculate lactate clearance. We compared initial lactate, lactate at 6 hours, and lactate clearance between the cirrhosis and non-cirrhosis groups. The primary outcome was in-hospital mortality. Results: Overall 777 patients were enrolled, of whom 91 had previously been diagnosed with cirrhosis. Initial lactate and lactate at 6 hours were both significantly higher in cirrhosis patients, but there was no difference between the groups in lactate clearance. A receiver operating characteristic curve analysis for predictors of in-hospital mortality revealed cut-off values for initial lactate, lactate at 6 hours, and lactate clearance of >4 mmol/L, >2 mmol/L, and <10%, respectively, among non-cirrhosis patients. Among patients with cirrhosis, the cut-off values predicting in-hospital mortality were >5 mmol/L, >5 mmol/L, and <20%, respectively. Neither lactate level nor lactate clearance was an independent risk factor for in-hospital mortality among cirrhotic and non-cirrhotic septic shock patients. Conclusions: The initial lactate level and lactate at 6 hours were significantly higher in cirrhosis patients than in non-cirrhosis patients.